The Rahmatan Lil-'Alamin Paradigm as an Approach to Islamic Education in Muhammadiyah Institutions - Khamam Khosiin; Tobroni Tobroni; Khozin Khozin (Universitas Muhammadiyah Malang, 2023)
This study examines the Rahmatan Lil-'Alamin paradigm as a distinctive Islamic approach to reshaping the educational environment in Muhammadiyah schools. The need to comprehend how this paradigm, which is based on the idea of universal compassion and justice, affects the pedagogical framework and ethos inside Islamic educational institutions connected to Muhammadiyah is what spurred the study's development. The methodology utilised in this study entails a thorough examination of curriculum papers, interviews with important figures in the field of education, and classroom observations at a few Muhammadiyah institutions. The study aims to comprehensively understand how the Rahmatan Lil-'Alamin paradigm is converted into educational practises, values, and learning outcomes within the Muhammadiyah school system by triangulating different data sources. The study's findings show that the Rahmatan Lil-'Alamin paradigm has been subtly woven into the instruction fabric at Muhammadiyah schools. This integration is clear in the curriculum's planning, instruction delivery, and creating a supportive and welcoming learning environment. The study also clarifies how this paradigm affects students' character development by promoting a feeling of societal duty, empathy, and ethical consciousness. By offering insights into the actual use of the Rahmatan Lil-'Alamin paradigm within Muhammadiyah institutions, this research contributes to the larger conversation on Islamic education. It not only draws attention to the distinctive characteristics of Islamic education within this paradigm but also emphasises how it can help achieve the larger objectives of comprehensive and socially responsible education within an Islamic framework.